Phylogeny of Rhigonematomorpha based on the complete mitochondrial genome of Rhigonema thysanophora (Nematoda: Chromadorea). (10th March 2014) - Kim, Taeho; Kim, Jiyeon; Cho, Soowon; Min, Gi‐Sik; Park, Chungoo; Carreno, Ramon A.; Nadler, Steven A.; Park, Joong‐Ki
<x xml:space="preserve">Abstract</x> We determined the complete mitochondrial genome sequence of Rhigonema thysanophora, the first representative of Rhigonematomorpha, and used this sequence along with 57 other nematode species for phylogenetic analyses. The R. thysanophora mtDNA is 15 015 bp and identical to all other chromadorean nematode mtDNAs published to date in that it contains 36 genes (lacking atp8) encoded in the same direction. Phylogenetic analyses of nucleotide and amino acid sequence data for the 12 protein‐coding genes recovered Rhigonematomorpha as the sister group to the heterakoid species, Ascaridia columbae (Ascaridomorpha). The organization of R. thysanophora mtDNA resembles the most common pattern for the Rhabditomorpha+Ascaridomorpha+Diplogasteromorpha clade in gene order, but with some substantial gene rearrangements. This similarity in gene order is in agreement with the sequence‐based analyses that indicate a close relationship between Rhigonematomorpha and Rhabditomorpha+Ascaridomorpha+Diplogasteromorpha. These results are consistent with certain analyses of nuclear SSU rDNA for R. thysanophora and some earlier classification systems that asserted phylogenetic affinity between Rhigonematomorpha and Ascaridomorpha, but inconsistent with morphology‐based phylogenetic hypotheses that suggested a close (taxonomic) relationship between rhigonematomorphs and oxyuridomorphs (pinworms). These observations must be tempered by noting that few rhigonematomorph species have been sequenced and included in phylogenetic analyses, and preliminary studies based on SSU rDNA suggest the group is not monophyletic. Additional mitochondrial genome sequences of rhigonematids are needed to characterize their phylogenetic relationships within Chromadorea, and to increase understanding of mitochondrial genome evolution.